Family-focused quality of life assessment and its implications for children’s social welfare: an ecological validity context - Grubliauskienė, Jūratė; Vaičekauskaitė, Rita; Babarskienė, Jurgita (Social Welfare: Interdisciplinary Approach, 2019)
The relationship between the quality of life and social welfare is of shared taxonomy, therefore it is difficult to define unambiguously. It is hard to imagine social welfare without the quality of life, but in order to put the quality of life into practice, we need the context of social welfare. For children’s social welfare, family and the way it creates quality of life is central. However, we lack instruments to evaluate children’s quality of life with family-focused approach. For that purpose, we introduce KIDSCREEN52 survey with 1763 children (aged 8-18 years old) and 1564 parents. Moreover, we raise the question of ecological validity, firstly, because there is a need to develop measurements that are closer to real life situations, in order to productively contribute to the ensuring of children’s social welfare.